Honokiol decreases alpha-synuclein mRNA levels and reveals novel targets for modulating alpha-synuclein expression - Fagen, Sara J.; Burgess, Jeremy D.; Lim, Melina J.; Amerna, Danilyn; Kaya, Zeynep B.; Faroqi, Ayman H.; Perisetla, Priyanka; DeMeo, Natasha N.; Stojkovska, Iva; Quiriconi, Drew J.; Mazzulli, Joseph R.; Delenclos, Marion; et al. (Frontiers in Aging Neuroscience, 2023)
Neuronal inclusions comprised of aggregated alpha-synuclein (αsyn) represent a key histopathological feature of neurological disorders collectively termed “synucleinopathies”, which includes Parkinson’s disease (PD). Mutations and amplifications in the SNCA gene encoding αsyn cause familial forms of PD and a large body of evidence indicate a correlation between αsyn accumulation and disease. Decreasing αsyn expression is recognized as a valid target for PD therapeutics, with down-regulation of SNCA expression potentially attenuating downstream cascades of pathologic events. Honokiol (HKL) is a polyphenolic compound derived from magnolia tree bark that has demonstrated neuroprotective properties. Here, we describe potential beneficial effects of HKL on αsyn levels in multiple experimental models. Using human neuroglioma cells stably overexpressing αsyn and mouse primary neurons, we demonstrate that HKL treatment results in a significant decrease in αsyn expression at both the protein and mRNA levels. Our data support a mechanism whereby HKL acts by post-transcriptional modulation of SNCA rather than modulating αsyn protein degradation. Additionally, transcriptional profiling of mouse cortical neurons treated with HKL identified several differentially expressed genes (DEG) as potential targets to modulate SNCA expression. Overall, these data highlight a viable strategy to reduce αsyn levels, which represents a promising target to modify disease progression in PD and other synucleinopathies. In addition, HKL acts as a powerful tool for investigating SNCA gene modulation and its downstream effects.